2020
DOI: 10.1080/2575517x.2020.1732733
|View full text |Cite
|
Sign up to set email alerts
|

Reducing suicidal ideation by biofeedback-guided respiration – heart rate coherence

Abstract: Background: Effectiveness of heart rate variability (HRV) biofeedback is dependent on the relationship between the measured respiratory-heart rate coherence (C HR ) and the resonant frequency (RFB) breathing. C HR is driven by the central autonomic network which consists of the interplay between the components of the autonomic nervous system, brainstem modulatory nuclei and cortical function. The extent to which heart rate is in coherence with respiratory frequency and the function of the central autonomic net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For instance, these indicators can be used to assess the mechanisms of therapeutic change [22], and to develop applications for predicting the suicide risk [111]. Similarly, techniques, such as the respiratory-heart rate coherence biofeedback, can be used as specific treatments in patients with suicidal behavior [112].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, these indicators can be used to assess the mechanisms of therapeutic change [22], and to develop applications for predicting the suicide risk [111]. Similarly, techniques, such as the respiratory-heart rate coherence biofeedback, can be used as specific treatments in patients with suicidal behavior [112].…”
Section: Discussionmentioning
confidence: 99%
“…One area of research has focused on the impact of biofeedback, such as breathing, targeted to change HRV in patients with mental health disorders. [23][24][25] This could be employed using a mobile application in conjunction with an alert for worsening HF HRV. Previous studies have shown the ability to utilize biofeedback guided by dynamic changes in HRV resulting in improved overall symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential interventions patients could implement upon receiving an alert. One area of research has focused on the impact of biofeedback, such as breathing, targeted to change HRV in patients with mental health disorders [ 23 - 25 ]. This could be employed using a mobile application in conjunction with an alert for worsening HF HRV.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of reduced PNS activity and increased SNS activity indicates more cardiac stress (Baevsky & Karnikova, 2017). The reverse is also true; Jelinek, and Khandoker, (Jelinek & Khandoker, 2020) found that by using biofeedback to raise PNS activity and lower SNS activity suicidal ideation was reduced in adolescent patients.…”
Section: Introductionmentioning
confidence: 99%